The Savi Learning Model with PMR Settings in Straight Line Equations Learning - Lasni Asri Entingunusa; Victor R. Sulangi; Santje M. Salajang (Jurnal Kajian dan Penelitian Umum, 2023)
This research was done to know student learning outcomes in junior high schools using the SAVI (Somatic, Auditory, Visual, Intellectual) learning model in the PMR (Realistic Mathematical Education Approach) setting. This study used a quasi-experimental method (Quasi-Experimental Design). In contrast, the sampling technique used was random cluster sampling using two classes, one as the experimental group class and one as the control group class. Data analysis techniques are normality tests, homogeneity tests, and hypothesis testing. Based on the study's results, it was found that there was an increase in student learning outcomes. The scores of student test results indicate this. Of 24 students who did not pass, only 2 people (5%) and 22 people (95%) passed. So that the results of the study concluded that the average student learning outcomes taught exceeded the minimum completeness criteria set by the school